How to buy individual bonds - Appel, Marvin (FT Press Delivers elements., 2010)
"This Element is an excerpt from Higher Returns from Safe Investments: Using Bonds, Stocks, and Options to Generate Lifetime Income (9780137003358) by Marvin Appel. How to safely buy individual bonds-and why the process can uncomfortably resemble buying a used car! Several things about buying bonds are not readily apparent on review of brokers' Web sites. First, unlike stocks, there is usually no specified commission per trade for buying bonds. Rather, buying bonds more closely resembles buying a car. The price you pay includes a profit for the dealer"--Resource description page.